IMPLEMENTASI PROGRAM WAJIB BELAJAR PENDIDIKAN DASAR 9 TAHUN : STUDI KASUS PADA PONDOK PESANTREN SALAFIYAH SYEKH BURHANUDIN KUNTU, KECAMATAN KAMPAR KIRI - GUSTRIVONI GUSTRIVONI; HASNAH FAIZAH; MARZUKI MARZUKI (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2017)
This research used a qualitative methodology. It revealed how the implementationof WajarDikdas program of 9 years. Collecting data with structural interview, observation anddocumentation, the data collected, analyzed and carried triangulation of sources and way to testdata validation. The results of this research was revealed through sub fokus of research.Thefirst : the produce implementation of establishment compulsory education program at salafiyahsheikh Burhanudin boarding school in accordance with juknis (guidelines), so it has been publishedbu the ministry of the religious establishment charter Kampar district, after going through itsphases and fulfilled the requirements and verify it.The seond : The progrogam curriculumcompulsory education taught six subjects in the national examination, they are : civic education,Indonesia language, English, natural science, sosial science and mathematics. Third : The learningprocess compulsory education program is implemented integrally with Islamic subjects just likeregular school, learning methods use active student learning (CBSA) in the classical style .students use student worksheets and textbooks.Fourth : the study of learning out comescompulsory education program implemented by educators such conduct daily test, unit of educationsemester exams and national exam held by government with regarding to cognitive, affective,psycomotoric aspects. Fifth : the educators compulsory education program already has gottenqualified education, diploma S1 (undergraduate). It does not have Islamic educators that teachno Islamic subjects. As well as the administrative staff already have gotten diploma or degree(minimum D3).The sixt : the parents perception towards the implementation of the conceptioncompulsory basic education program is possitve and accommodate the wishes of parent’s so itcan increase the number of student significantly.